Determination of copper at trace levels in fennel tea samples by flame atomic absorption spectrometry after the implementation of simultaneous complexation and supramolecular solvent based spraying assisted liquid phase microextraction - Tutar, Bahar Karademir; Tutar, Omer Faruk; Bodur, Suleyman; Derin, Yavuz; Tutar, Ahmet; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
A simple and efficient preconcentration method named as supramolecular solvent based spraying assisted liquid phase microextraction (SUPRAS-SA-LPME) was combined with a flame atomic absorption spectrometry (FAAS) for the determination of copper in fennel tea samples at trace levels. An alkanol (1-decanol)/THF based SUPRAS (containing complexation agent) was used as extraction solvent instead of traditional organic solvents for the first time in an SA-LPME process. Under the optimum conditions, system analytical performance of the developed method was evaluated, and limit of detection (LOD)/limit of quantitation (LOQ) values were recorded as 1.91/ 6.37 mu g kg-1. After the evaluation of system analytical performances, the enhancement in detection power/ calibration sensitivity was found to be 21.3/21.8 folds when the comparison of LOD values/calibration plot slopes of the FAAS and SUPRAS-SA-LPME-FAAS systems. The method applicability was tested for the fennel tea samples by spiking experiments, and acceptable recovery results (80.2% - 111.8%) were obtained for low, mid and high spiked concentration levels.
Keywords: Copper; Fennel tea; Microextraction; Supramolecular solvent; Thiosemicarbazone; ENVIRONMENTAL-SAMPLES; WATER SAMPLES; PRECONCENTRATION; EXTRACTION; IRON; FAAS; Chemistry; Food Science & Technology